Leaders - Nixon, Richard; Translated by Naeem Tariq (Lahore FIction House, 2018)
Contains sketches of the following world leaders: Winston Churchill, Charles deGaulle, Douglas MacArthur and Shigeru Yoshida, Konrad Adenauer, Nikita Khrushchev, Zhou Enlai.
Keywords: World politics -- Statesmen -- Nixon, Richard M. (Richard Milhous), 1913-1994